Biaxial constitutive relationship and strength criterion of composite fabric for airship structures. (15th April 2019) - Shi, Taibai; Chen, Wujun; Gao, Chengjun; Hu, Jianhui; Zhao, Bing; Wang, Ping'an; Wang, Mei
Abstract: Given their irreplaceable advantages such as high strength-to-weight ratio, composite fabrics have been widely applied and studied. However, due to the limitation of specimen design and test procedure, integral biaxial constitutive relationships and valid failure criteria of composite fabrics were unavailable while desirable. In this study, typical composite fabrics for airship structures were employed to manufacture self-designed double-layer cruciform specimens as biaxial tensile tests were performed subsequently. Since the stiffness of the specimen was reasonably distributed, biaxial tensile failure characterizing the biaxial tensile strength under various warp-to-weft stress ratios was acquired. Two failure modes, the cross slits rupture and the single slit breakage, occurred when specimens reached load-bearing capacities. Furthermore, the digital image correlation approach was utilized to record the strain field during the whole test process. According to the test data, integral stress-strain curves and analytical biaxial stress-strain response surfaces were calibrated, developed and interpreted thoroughly. Since significant deviation was observed in previous failure criteria for rigid composite materials, a novel biaxial failure criterion was firstly proposed which could perfectly comply with the failure envelope obtained from the test results. As the accuracy of the failure criterion was verified, physical, mechanical and mathematical explanations for the novel failure criterion were finally illustrated.